2017
DOI: 10.1177/0001839217736045
|View full text |Cite
|
Sign up to set email alerts
|

Posting and Slotting: How Hiring Processes Shape the Quality of Hire and Compensation in Internal Labor Markets

Abstract: Recent research highlights the benefits of internal hiring-filling a job by hiring a worker currently employed by the organization-and more than half of jobs are filled that way. Yet we know surprisingly little about the processes that facilitate the movement of workers across jobs within firms. I address this gap by first detailing the portfolio of internal hiring processes employed by large organizations, focusing on posting and slotting. Posting is a predominantly market-based process in which a manager pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 99 publications
0
40
0
2
Order By: Relevance
“…In addition, the effect of relationship-based concerns is not limited to cases of triadic exchange—research on negotiations has found that individuals sacrifice economic gains to preserve their relationship with exchange partners (Curhan, Elfenbein, and Xu, 2006). For example, recent labor market research has suggested that new hires are less likely to negotiate for higher starting salaries when they are slotted, or hand-picked, for a position by the hiring manager (Keller, 2018).…”
Section: Audience-based Mechanisms Of Gender Bias In Triadic Exchangementioning
confidence: 99%
“…In addition, the effect of relationship-based concerns is not limited to cases of triadic exchange—research on negotiations has found that individuals sacrifice economic gains to preserve their relationship with exchange partners (Curhan, Elfenbein, and Xu, 2006). For example, recent labor market research has suggested that new hires are less likely to negotiate for higher starting salaries when they are slotted, or hand-picked, for a position by the hiring manager (Keller, 2018).…”
Section: Audience-based Mechanisms Of Gender Bias In Triadic Exchangementioning
confidence: 99%
“…Moreover, in such low-skilled blue-collar contexts sophisticated recruitment processes for internal and external hires are not widespread, and individuals are recruited mainly out of need for further human capital, without considering the (demographic) fit to the team (Brown, Dickens, Gregg Paul, Machin, & Manning, 2001;Keller, 2017). This creates an environment where individuals, especially non-traditional team members, face difficulties in adjusting to their team and are more likely to experience negative contact.…”
Section: The Time-varying Effect Of Demographic Dissimilaritymentioning
confidence: 99%
“…Some characteristics of our sample (i.e., lack of systematic staffing and socialization procedures), as well as past research findings on diversity-friendly climates and leadership, suggest that companies should attend to the temporal patterning of demographic dissimilarity effects and complement their diversity-friendly recruitment strategies in at least three ways. First, companies might consider using structured recruitment and transfer processes also for lowskilled blue-collar jobs and internal hires (Keller, 2017). Involving the supervisor and potentially also the other members of the recipient team in newcomer selection might heighten their sensitivity to successful integration of demographically dissimilar newcomers and lower the risk of perceptions of negative anchoring events for the newcomers.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…The processes that organisations use to hire internally—the way that over half of positions are still filled—also influence employability. Organisations use both market-like internal job postings and ‘slotting’, where managers fill positions with people they hand-pick,20 showing how job mobility might be driven by managers and organisations, as well as workers.…”
Section: Mobility and Employabilitymentioning
confidence: 99%